Efficacy of high dose of magnesium sulphate for cardiac arrhythmias in patients of wheat pill poisoning - Hassan, Abdul Wahab; Meo, Muhammad Hussain; Saqib, Muhammad Najam; Saleem, Nasreen Muhammad (Journal of Postgraduate Medical Institute, 2013)
Objective: To study the prophylactic effects of High Dose Magnesium Sulphate on Cardiac Arrhythmias,Cardiogenic shock and associated mortality in Cases of Aluminum Phosphide Poisoning. Methodology: Seventy One patients of wheat pill poisoning were randomly selected. Thirty seven weregiven high dose of Magnesium Sulphate (study group) and 34 were given low dose of magnesium sulphate(control group) through intravenous route along with other supportive measures. Patients were observedfor cardiac arrhythmias and mortality in both groups. Study end point was safe discharge from the hospitalor death. Results: The mean age of the sample was 25.27+7.48 years. Frequency of cardiac arrhythmias was 40.54%(n=15) in study group versus 55.88% (n=19) in the control group. Average length of stay and frequency ofcardiogenic shock was slightly lower in the study group, i.e., 1.42+0.65 days while it was 1.78+1.38 daysfor the control group. Overall, mortality in both the groups was 66.20% (n=47), which remained almostequal in both groups or slightly favored study group with 64.86 % (n=24) in the study and 67.65% (n=23)in the control group. Conclusion: High dose magnesium sulphate administration was found to be helpful for cardiac arrhythmiaand shock but mortality remained unchanged.